Effects of in-competitive season power-oriented and heavy resistance lower-body training on performance of elite female water polo players - Veliz, R. R.; Suarez-Arrones, L.; Requena, B.; Haff, G. G.; Feito, J.; Saez de Villarreal, E. (The Journal of Strength and Conditioning Research, 2015)
We examined the effect of 16 weeks of lower-body resistance and power-oriented training on key performance measures of elite female water polo players. Twenty-one players were randomly assigned to 2 groups: control group (C) who did in-water training only and a lower body strength (LBS) group, who performed resistance (full squat and split squat) and jump and power-oriented lower-body training (countermovement jump [CMJ] loaded and CMJ) sessions (twice per week) in addition to the same in-water training. In-water training was conducted 5 days per week for a total of 16 weeks. Twenty-meter maximal sprint swim (MSS), lower-body strength during 1 repetition maximum (1RM) full squat (FS), in-water boost and CMJ, and Throwing speed (ThS) were measured before and after the training. Pretraining results showed no statistically significant differences between the groups in any of the variables tested. After 16 weeks, no statistically significant improvement was found in any of the variables measured in the C group, however, significant improvement was found in the LBS group: in-water boost (4.6 cm, 12.02%, effect size [ES] = 1.02), CMJ (2.4 cm, 8.66%, ES = 0.85), FS (12.7 kg, 20.99%, ES = 2.41), and ThS (3.4 km/h, 6.86%, ES = 3.44). Lower-body resistance and power-oriented training in female water polo players for 16 weeks produced significant improvements in performance qualities highly specific to water polo performance. Therefore, we propose modifications to current training methodology for female water polo players to include resistance and power-oriented training during the competitive season in this sport.